Analisis Materi Ajar PAI Integratif Di Perguruan Tinggi Umum - Afriani, Risa; Fadriati; Azizah, Nur (STAI Ihyaul Ulum Gresik, 2024)
Integrative PAI teaching materials in public universities are currently used as material taught in general courses at PTU. Integrative PAI teaching materials are PAI teaching materials that examine one scientific field by utilizing other scientific fields and show the interrelationships between various scientific disciplines, so that students know the reasons why religion allows or prohibits someone from doing something seen from the aspects of various scientific disciplines related to the teaching material. and students can see the connection between these sciences. Therefore, PAI teaching materials are very important to be implemented in public universities. This Islamic Religious Education course explores human and religious study material, Islamic teachings and their practice in life, Islam and Islamic discourse and their implementation in religious life, society and nation, as well as in work. This course is intended to encourage students to strengthen their faith and piety, develop noble morals and make Islamic teachings a basis for thinking and behaving in work and developing their profession, by using the Qur'an as a guide to life and as a basis for scientific construction